Utilization of Low Value Fish - 1. Preparation of Fish Fingers from Croaker and Perches - Reddy, Lakshminatha; T.M.R., Shetty; K.C., Dora (Fishery Technology, 2025)
A method for the preparation of fish fingers from croaker and pink perch meat has been developed. The recipe, ingredients for the paste, batter and the breading mix have been standardised through taste panel studies. An extrusion technique has been used to make fish fingers to the required size and shape rather than sawing of the frozen meatblocks generally followed.